Modernization of Islamic Philanthropy: Analysis of The Business Model Canvas of Rumah Zakat in the Era of Digitalization - Nurul Alvi Chindi Fadhilah; Muhamad Zen; Fatmawati (Faculty of Islamic Economics and Business, Madura Islamic State University, 2026)
Abstract Purpose – This Study Analyzes the transformation of Rumah Zakat’s digital business model through the Business Model Canvas (BMC) framework in the era of digitalization. Methodology – This research method uses a qualitative approach through document analysis (literature study) on various scientific literature, performance reports, websites, as well as internal analysis drafts regarding Rumah Zakat that have been published. Findings – Rumah Zakat achieved a governance score of 0.84 and a distribution effectiveness of 91.31%. although digital infrastructure invesment triggered fundraising costs of 108.95%, this system managed to maintain donor retention at 88%. Implications – System automation is required to reduce high operational costs while still maintaining Sharia compliance and the humanistic aspect of service. Originality – A cutting-edge strategic evaluation (up to 2026) of the digital transformation of zakat instituitions that integrates the BMC framework with the principles of Maqasid Sharia.